EFFECT OF LEARNING STRATEGIES AND CONCEPT MAPS THINKING STYLE LEARNING OUTCOMES OF STUDENTS ISLAMIC EDUCATION OF JUNIOR HIGH SCHOOL AL WASHLIYAH 4 MEDAN. - Candra Wijaya, Edi Saputra, Taufiq Marpaung (Pascasarjana UIN Sumatera Utara, 2019)
The purpose of this study was to determine and describe: (1) Islamic Education learning results ofstudents who are taught to use concept maps different learning strategies with learning outcomes ofstudents who were taught using expository learning strategies, (2) The results of studying history istaught in Islamic Education learning strategy map concept is higher than in the Islamic Educationlearning outcomes of students who are taught with the expository teaching strategies for students whohave a style of thinking skuensial, (3) the Islamic Education learning that are taught with the learningstrategy map concept is higher than the results of learning Islamic Education who taught studentswith expository teaching strategies for students who have a random thought style, and (4) the interactionbetween learning strategies and thinking styles on learning outcomes of the Islamic Education.